Understanding the mechanisms of HPV-related carcinogenesis: Implications for cell cycle dynamics. (7th November 2022) - Sund, Derrick T.; Brouwer, Andrew F.; Walline, Heather M.; Carey, Thomas E.; Meza, Rafael; Jackson, Trachette; Eisenberg, Marisa C.
Abstract: The role of human papillomavirus (HPV) as a causative agent for epithelial cancers is well-known, but many open questions remain regarding the downstream gene regulatory effects of viral proteins E6 and E7 on the cell cycle. Here, we extend a cell cycle model originally presented by Gérard and Goldbeter (2009) in order to capture the effects of E6 and E7 on key actors in the cell cycle. Results suggest that E6 is sufficient to reverse p53-induced quiescence, while E7 is sufficient to reverse p16 INK4a -induced quiescence; both E6 and E7 are necessary when p53 and p16 INK4a are both active. Moreover, E7 appears to play a role as a "growth factor substitute", inducing cell division in the absence of growth factor. Low levels of E7 may permit regular cell division, but the results suggest that higher levels of E7 dysregulate the cell cycle in ways that may destabilize the cellular genome. The mechanisms explored here provide opportunities for developing new treatment targets that take advantage of the cell cycle regulatory system to prevent HPV-related cancer effects. Highlights: We developed a model of the effects of HPV on key actors in the cell cycle. Model results suggest that E6 is sufficient to reverse p53-induced quiescence. Simulations show E7 is sufficient to reverse p16-INK4a-induced quiescence. We also show that both E6 and E7 are necessary when p53 and p16-INK4a are both active. E7 may act as a growth factor substitute, inducing cell division sans growth factor.